PEMANFAATAN LIMBAH CANGKANG TELUR, KULIT BAWANG DAN DAUN KERING MELALUI PROSES SAINS DAN TEKNOLOGI SEBAGAI ALTERNATIF PENGHASIL PRODUK YANG RAMAH LINGKUNGAN - Rahmadina Rahmadina; Efrida Pima Sari Tambunan (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2017)
The purpose of this study was to ascertain that the processing of waste egg shells, onion skins, and dried leaves can be organic fertilizer through the process of science and technology as a product that is environmentally friendly and high economic value. This research method is descriptive only quantitative. Research results showed that the waste chicken egg shells, onion skins, and dried mango leaves can be processed into organic fertilizer with high levels of nutrients for organic fertilizer from the eggshell is N 0.18% (medium), P content of 7% (medium) , and levels of C 8% (moderate), substance C - Organic 5.2% (very high), C / N of 30 (very high), for fertilizers from onion skin that is N 0.13% (moderate), the levels of P 4 % (moderate), and levels of C 5% (medium), substance C - Organic 4.8% (high), C / N 23 (high), for fertilizers from the dried leaves are N 0.16% (medium), P content of 6% (moderate), and K content of 5.8% (moderate), substance C - Organic 4% (high), C / N 25 (high), that is worth selling high and can compete, Marketing is done in a flower sales with sales revenue was approximately 8 burlap sack 5 kg of the total sales of 12 jute from each - each organic fertilizer.